Optimization of the process of obtaining epoxidized natural rubber for the development of new composite materials on its basis - Zybaylo, Sergiy; Ved, Viktor; Okhtina, Oxsana; Kiselev, Vadym; Shapovalov, Denis (Technology audit and production reserves, 2019)
The object of research is the process of epoxidation of natural rubber scrap. Epoxidized natural rubber (ENR) has a wide range of applications, for example, in treadmill coatings, special tires, belt drives, hoses, shoes, adhesives, sealants, floor coverings and other areas where only special synthetic rubbers are used. Natural rubber (NR) is modified by the epoxidation reaction to achieve higher oil resistance, increased adhesion, weather resistance and damping characteristics of materials with its use. Promising is the processing of secondary, non-standard, natural rubber (scrap) as a raw material for the ENR production. Thus, the task of scrap disposal and its return to the production cycle is solved. To accomplish the task of epoxidation of secondary rubber, the possibility of conducting combined physicochemical processes in a two-phase water-xylene medium in one reaction space was studied to reduce the total energy costs. The use of a combined reaction-separation process for the epoxidation of scrap of natural rubber allows to solve the problem of accumulation and disposal of rubber waste in the most efficient way. It is possible to obtain a product with a regulated functionalization degree without a significant amount of by-products. To find the optimal regime for conducting the combined reaction-separation process of epoxidation, the method of the planned experiment was used to obtain the regression equation with its subsequent analysis. The obtained regression equation makes it possible to optimize the conditions for conducting the process of epoxidation of nanocrystals with obtaining products with desired properties. As a result of the implementation of the planned experiment, it is found that epoxidation at a temperature of 93 °C of a diluted (10 % wt.) solution of natural rubber with peracetic acid formed "in situ" provides a higher epoxidation degree. The conditions and ratios of the components are selected under which NR retains aggregative stability during epoxidation in a water-xylene medium.